2021
DOI: 10.4149/bll_2021_060
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neutrophil/lymphocyte ratio and uric acid levels in multiple sclerosis patients

Abstract: BACKGROUND: In this study, we aimed to determine whether neutrophil / lymphocyte ratio (NLR), obtained by dividing the number of neutrophils by the number of lymphocytes, and uric acid (UA) levels in multiple sclerosis (MS) patients vary compared with healthy controls and to establish correlations among these changes themselves as well as between such changes and MS subtypes, immunomodulatory drug use, the duration of the disease and prognosis. METHODS: 150 patients who presented to our hospital and were diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, the relationship between UA and NLR remains controversial. For example, in a study of multiple sclerosis, NLR was found to be negatively correlated with UA ( Bolayir et al, 2021 ). The same study also found that co-assessment of NLR and UA may be more effective than assessing these parameters individually in demonstrating disability in multiple sclerosis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between UA and NLR remains controversial. For example, in a study of multiple sclerosis, NLR was found to be negatively correlated with UA ( Bolayir et al, 2021 ). The same study also found that co-assessment of NLR and UA may be more effective than assessing these parameters individually in demonstrating disability in multiple sclerosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…And it is a simple, inexpensive, and useful tool to indicate subclinical low-grade inflammation in many systemic circumstances ( Taşoğlu et al, 2016 ). The UA level is closely related to inflammation indicators ( Ruggiero et al, 2006 ; Kocaman et al, 2009 ; Liu et al, 2019 ; Bolayir et al, 2021 ); for example, a community-based study showed that inflammation indicators are positively correlated with UA, and this association is independent of the usual risk factors for chronic kidney disease (CKD) ( Liu et al, 2019 ). However, the relationship among ischemic stroke recurrence, UA level and NLR is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Other current pathogenesis incriminated in the onset and progression of already mentioned diseases are epithelial-to-mesenchymal transition in renal tubular cells, renal vasoconstriction mediated by endothelial dysfunction, and activation of renin-angiotensin system (RAAS) [ 12 ]. Some studies reported that high levels of uric acid may exert protective effects in neurological disorders, such as Parkinson’s disease [ 13 ], multiple sclerosis [ 14 , 15 ], Alzheimer’s disease [ 16 ], and vascular-disease-related dementia [ 2 ] through its extracellular anti-oxidative role. In contrast, some researchers sustain the hypothesis that deterioration of kidney function associated with hyperuricemia might be due to co-existing conditions, such as vascular calcifications, hypertension, and obesity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…RDW, PLR, MLR, MPV, RDW, NLR, and SII were calculated by using CBC parameters. These parameters are used as new inflammatory markers, which are considered as cost-effective and simple laboratory parameters indicating systemic inflammation in many diseases.. 5,13,14 This study aimed to explore inflammatory and CBC parameters in patients with SD and evaluate their possible relationship with disease severity (SDASI). To the best of our knowledge, this study is the first to investigate the relationship between disease severity and these markers.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are used as new inflammatory markers, which are considered as cost‐effective and simple laboratory parameters indicating systemic inflammation in many diseases. 5,13,14 …”
Section: Discussionmentioning
confidence: 99%